Off-label use of transmucosal ketamine as a rapid-acting antidepressant: a retrospective chart review - Nguyen L (Dove Medical Press, 2015)
Linda Nguyen,1,2 Patrick J Marshalek,2 Cory B Weaver,1 Kathy J Cramer,2,3 Scott E Pollard,2,4 Rae R Matsumoto1,2,5 1Department of Pharmaceutical Sciences, School of Pharmacy, West Virginia University, Morgantown, WV, USA; 2Department of Behavioral Medicine and Psychiatry, School of Medicine, West Virginia University, Morgantown, WV, USA; 3Doctor of Nursing Practice Program, Robert Morris University, Moon Township, PA, USA; 4Department of Behavioral Health, West Park Hospital, Cody, WY, USA; 5College of Pharmacy, Touro University California, Vallejo, CA, USA Objective: This study evaluated the effectiveness and safety of subanesthetic doses of ketamine using an off-label, transmucosal administration route in patients with treatment-resistant depression.Methods: A retrospective chart review was conducted to identify patients who met the inclusion criteria for treatment-resistant major depressive disorder. Seventeen such patients who received subanesthetic doses of ketamine were included. Patient demographics, efficacy (drug refill, clinician notes), side effects, and concurrent medications were assessed.Results: Benefit from low-dose transmucosal ketamine was noted in 76% of subjects (average age 48 years, 88% female), with a dose duration lasting 7–14 days. No notable side effects were noted. The most common classes of concurrent medications to which ketamine was added were serotonin–norepinephrine reuptake inhibitors (59%), stimulants (47%), folate replacement (47%), and benzodiazepines (47%).Conclusion: Our results provide preliminary evidence of the effectiveness and safety of low-dose transmucosal ketamine in treatment-resistant patients. A controlled, prospective pilot study is warranted to validate these findings. Keywords: ketamine, depression, treatment resistance, NMDA receptor, glutamate, mood disorder